Historic Doubts on the Life and Reign of King Richard the Third - Walpole, Horace, 1717-1797 (Salt Lake City, UT : Project Gutenberg, 2005)
"Historic Doubts on the Life and Reign of King Richard the Third" by Horace Walpole is a historical account written in the late 18th century. The work critically examines the widely accepted narrative of Richard III's life and reign, challenging the established characterizations of him as a tyrant. The book seeks to unravel the layers of historical misrepresentation surrounding Richard III, suggesting that much of what is believed about him might stem from bias and conjecture rather than fact. At the start of the text, Walpole lays out his intention to scrutinize the credibility of traditional historians and their claims regarding Richard III's alleged crimes, including the murders of several prominent figures. He contemplates the qualifications and potential biases of these historians while detailing how history is often written by those with ulterior motives. Walpole introduces a critical lens through which he evaluates the veracity of historical accounts and highlights the lack of solid evidence to substantiate the darker aspects of Richard's reputation, thus setting the stage for an argument aimed at reassessing Richard III's legacy. (This is an automatically generated summary.)
Release date is 2005-12-28
E-text prepared by Marjorie Fulton
Keywords: Great Britain -- History -- Richard III, 1483-1485; Richard III, King of England, 1452-1485 -- Early works to 1800; Great Britain -- Kings and rulers -- Biography -- Early works to 1800